Konseptualisasi Media Pembelajaran Microsoft Sway pada Pembelajaran Toleransi Umat Beragama dalam PAI - Nabila Azzahra; Nurmawati (YASIN, 2026)
Although the implementation of information and communication technology (ICT)-based instructional materials in Islamic education has been widely studied, research that explicitly integrates learning needs analysis with the use of Microsoft Sway for religious tolerance material remains limited. This study aims to analyze ICT-based learning needs and establish a conceptual foundation for designing Microsoft Sway-based instructional materials on religious tolerance. The study employed a qualitative approach with a descriptive design involving one Islamic Religious Education teacher and three students selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation and were subsequently analyzed using the qualitative data analysis model of Miles, Huberman, and Saldaña. A conceptual analysis was also conducted by integrating findings from previous studies and relevant theories. The findings indicate that ICT-based instructional materials are needed to enhance conceptual understanding, encourage students’ active participation, accommodate flexible learning needs, and create engaging and comprehensive learning experiences. Based on these needs, Microsoft Sway-based instructional materials were conceptually designed by integrating various multimedia learning elements into a single platform. This study emphasizes that learning needs analysis is an important initial stage in the development of effective instructional media. The findings broaden the understanding of digital media use in Islamic education and provide practical guidance for Islamic Religious Education teachers in designing interactive and student-centered instructional materials. The findings may also serve as a foundation for further research on the development and testing of Microsoft Sway-based instructional materials.